Mechanisms of T-cell Depletion in Tumors and Advances in Clinical Research - Xiangfei Su; Mi Zhang; Hong Zhu; Jingwen Cai; Zhen Wang; Yuewei Xu; Li Wang; Chen Shen; Ming Cai (Biological Procedures Online)
Abstract T lymphocytes (T cells) are essential components of the adaptive immune system that play a vital role in identifying and eliminating infected and tumor cells. In tumor immunotherapy, T cells have emerged as a promising therapeutic strategy due to their high specificity, potent cytotoxic capability, long-lasting immune memory, and adaptability within immunotherapeutic approaches. However, tumors can evade the immune system by depleting T cells through various mechanisms, such as inhibitory receptor signaling, metabolic exhaustion, and physical barriers within the tumor microenvironment. This review provided an overview of the mechanisms underlying T-cell depletion in tumors and discussed recent advances in clinical research related to T-cell immunotherapy for tumors. It highlighted the need for in-depth studies on key issues such as indications, dosage, and sequencing of combined therapeutic strategies tailored to different patients and tumor types, providing practical guidance for individualized treatment. Future research on T-cell depletion would be necessary to uncover the fundamental mechanisms and laws of T-cell depletion, offering both theoretical insights and practical guidance for the selection and optimization of tumor immunotherapy. Furthermore, interdisciplinary, cross-disciplinary, and international collaborative innovations are necessary for developing more effective and safer treatments for tumor patients.